THE FUNCTION OF IDEAL LAW IN PREPARATION REGULATION LEGISLATION IN ORDER TO CREATING EQUITABLE REGIONAL DEVELOPMENT - Retno Saraswati (Fakultas Hukum, Universitas Diponegoro, 2017)
Indonesia as a country that adheres to the concept of the welfare of the duty of the welfare, in order to achieve the necessary guidance in the formation of the law, in the form of legal ideas. Indonesia has set a goal of Pancasila as the law, which includes the noble values developed from their own community. Efforts to create equitable regional development can be achieved through legislation that is based on the ideals of the law.